Effect of interfacial microstructure on the mechanical properties of GNPs/Al composites. (June 2020) - Ju, Boyu; Yang, Wenshu; Shao, Puzhen; Hussain, Murid; Zhang, Qiang; Xiu, Ziyang; Hou, Xuwei; Qiao, Jing; Wu, Gaohui
Abstract: The interfacial bonding affects the performance of Graphene/Al matrix composites significantly. However, the relationship between interfacial structure and mechanical properties has not been fully understood yet. In the present work, the GNPs/Al composites were prepared by pressure infiltration method, and the interface structure of Graphene-Al2 O3 –Al and graphene-(Al4 C3, Al2 OC)–Al was prepared by addition of polydimethylsiloxane (PDMS) as process control agent (PCA). The tensile strength of the GNPs/Al composite material with Al2 O3 interfacial bonding was 303 MPa, which was about 30% higher than that with Al4 C3 and Al2 OC interface. Moreover, calculated by first-principle, it has been found that the interfacial shear strength of the graphene-Al2 O3 –Al interface (378 MPa) was much higher than that of graphene-Al (37 MPa), graphene-Al4 C3 (83 MPa) and graphene-Al2 OC (66 MPa), which leads to the improved mechanical properties. Graphical abstract: Image 10749